Globalizing Indonesia’s hijab fashion centre as state’s national interest: a critical appraisal - Elvianti, Witri; Putri, Nanda Amedina (Universitas Muhammadiyah Yogyakarta, 2019)
Despite the past experiences which banned the praxis of hijab and Islamic dress code in Indonesia, the government of Indonesia currently unveiled its vision to form the country as a global Mecca of hijab and Muslim fashion. The decision formulated by Joko Widodo ? that remained representative of secularist yet nationalist ideology ? rather implied the presence of state in admitting the praxis of hijab and Islamic dress code as its potential means to achieve national interest. Therefore, the analyst sought to address why state eventually desires to establish Indonesia as a global capital of hijab and Muslim fashion in 2020. With reference to the neo liberal international political economy, the analyst came to argue that due to the liberalization in national economy and the world economy transformation the current government consolidated with the issue of hijab and Muslim fashion trend as it promises the development of individual freedom in textile industries. In ways of making Indonesia a newly industrial country in 2020, the government has to find any potential comparative advantage by which the industrial hijab and Muslim fashion that could offer. Key words: hijab, Muslim fashion, industrialization, liberalization, international political economy, Indonesia?s government.